Pro brain natriuretic peptide (BNP) hormone and tissue Doppler abnormalities in patients with homozygous sickle cell disease in Bahrain: echocardiographic study - Garadah, Taysir; Hassan, Adla B; Jaradat, Ahmed A; Sequeira, Reginald P; Alajmi, Abdulla (International Journal of Medicine, 2014)
Background: Pulse Doppler echocardiography has a diagnostic value in right and left ventricular function in patients with homozygous sickle cell disease (SCD), however the role of the tissue Doppler is unclear. Aim: To evaluate the diagnostic role of tissue Doppler in the assessment of right ventricle (RV) and left ventricular function in adult patients with SCD. And to study the prevalence of pulmonary hypertension (PAH) in patients with SCD using the tricuspid valve velocity on echocardiogram. Method: Seventy patients with homozygous SSD were compared with healthy control. Every patient had clinical assessment, had pulsed and tissue Doppler evaluation, in addition to assessing serum level of hemoglobin, ferritin and pro Brain Natriuretic Peptide (BNP). The mean difference between the two groups for tissue Doppler and biometric variables was assessed. Results: Seventy patients had SCD (mean age 28 years, 14-40) and 54 (77%) were males. The age and gender proportions were similar in both groups. Patients with SCD compared with the control had significantly low diastolic pressure, lower hemoglobin level, but high serum ferritin and pro BNP hormone. Furthermore, there was a significant increase in the diameter of left atrium, higher left ventricle mass index, and higher right ventricle diameter and wall thickness. The left ventricle ejection fraction percentage was similar between both groups, but SCD had significantly higher right ventricle tricuspid annular plane systolic excursion (TAPSE) of 1.42±0.21 vs. 1.11±0.23 cm (P= 0.02). The RV pulsed Doppler data showed restrictive filling pattern with significantly higher E wave, high E/A ratio and short Deceleration time ; likewise, the upper pulmonary vein systolic/diastolic velocity was significantly lower 1.5 ±0.12 vs. 2.4±0.11cm (p=0.002). The tissue Doppler of lateral annulus of tricuspid valve and the septum mitral annulus in SCD patients showed a significant lower S wave, higher E/E- ratio and lower A wave. The incidence of pulmonary hypertension in SCD patients via tricuspid valve regurgitation (TVR) velocity of >2.6 m/s was 22 %. There was a positive correlation between serum level of ferritin, pro BNP and tricuspid valve regurgitation velocity (r=0.35) and (r=0.43) respectively. Conclusion: Adult patients with SCD have included right ventricular diameter and increased RV wall thickness. The LV systolic function is normal but with RV systolic and diastolic dysfunction that was suggestive of restrictive pattern. The incidence of pulmonary hypertension in SCD was 22% with positive correlation between serum level of ferritin, pro BNP and the development of pulmonary hypertension. Keywords: Sickle Cell Anemia, Tissue Doppler, Bahrain.